Generalized Structural Description of Calcium–Sodium Aluminosilicate Hydrate Gels: The Cross-Linked Substituted Tobermorite Model - Myers, Rupert J; Bernal, Susan A; San Nicolas, Rackel; Provis, John L (Langmuir, 2013)
Structural models for the primary strength and durability-giving reaction product in modern cements, a calcium (alumino)silicate hydrate gel, have previously been based solely on non-cross-linked tobermorite structures. However, recent experimental studies of laboratory-synthesized and alkali-activated slag (AAS) binders have indicated that the calcium–sodium aluminosilicate hydrate [C-(N)-A-S-H] gel formed in these systems can be significantly cross-linked. Here, we propose a model that describes the C-(N)-A-S-H gel as a mixture of cross-linked and non-cross-linked tobermorite-based structures (the cross-linked substituted tobermorite model, CSTM), which can more appropriately describe the spectroscopic and density information available for this material. Analysis of the phase assemblage and Al coordination environments of AAS binders shows that it is not possible to fully account for the chemistry of AAS by use of the assumption that all of the tetrahedral Al is present in a tobermorite-type C-(N)-A-S-H gel, due to the structural constraints of the gel. Application of the CSTM can for the first time reconcile this information, indicating the presence of an additional activation product that contains highly connected four-coordinated silicate and aluminate species. The CSTM therefore provides a more advanced description of the chemistry and structure of calcium–sodium aluminosilicate gel structures than that previously established in the literature.